Sistem Inventory Gudang pada PT. Manaaji Asapena Mitraabadi - Fajar Rachmat Saputra; Harfebi Fryonanda (UNIVERSITAS KALBIS, 2022)
Recording on every transaction is very important for the company, because with the recording, the company can find out the availability of goods and data on incoming and outgoing goods. With a manual recording system that allows data redundancy and lost data, so that it can harm the company, therefore researchers conduct research and development systems at PT Manaaji Asapena Mitraabadi so that the recording system can be done computerized so that recording can be done efficiently. This research was conducted using prototyping methods and run on a web browser. The language used in developing this application is the programming language HTML, PHP, and Java.